Desvendando padrões estruturais, efeito do tamanho e isolamento de fragmentos florestais na florística, na riqueza e diversidade em Alter do Chão, na Amazônia Oriental Brasileira. - Amaral, Iêda Leão do (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Old Forest Fragments (FF) that occur in the Amazon have been scarcely studied, especially the ones embedded in savannas. The existing approaches mostly targeted the fragments that occur on the basin edges, get flooded (river islands), or in the octone region between the Amazon Forest and the Central Brazil Cerrado. There are practically no studies addressing the flora on forest fragments embedded in the savanna in Alter do Chão, those that may be found are focused on fauna, both entomofauna, mesofauna, avifauna and macrofauna. Therefore, the present study seeks to evaluate the influence extrinsic variables like fragment isolation, size, distance to the continuous forest (DCF) and distance from the water (DW) exert on the composition, richness and floristic diversity, as well as plant communities structure and abundance. Then, it aims to compare the fragmented communities findings with those from the Semideciduous Seasonal Forest sorrounding the savanna. The evaluation was carried out in 25 forest fragments, in which four, 2x250 m subplots were implemented. The same procedure was employed on the nine continuous forest samples. Individuals were included according to the minimum criterion of 4 cm breast height circumference (BHC) corresponding to 1.27 cm at breast height diameter (BHD), 1.30 above the ground, numbered, identified with aluminum tags and botanical samples collected for species identification. Plant density and species richness were compared between forest fragments and continuous forest, by t-test, and composition differences by cluster analysis linear regression was used to assess the influence forest fragments size and distance to the continuous forest on basal area and diameter. Alpha diversity was estimated by the Fisher alpha index, which has shown to be little influenced by sample size and, by multiple linear regression to investigate which factors had exerted any influence on the predictors-analyzed forest fragments alpha (α) diversity and species richness variation: 1) Forest fragments size (S); 2) continuous forest distance (CFD) and 3) water distance (WD). Floristic composition changes evaluation was performed through analysis of substitution and nesting processes, applying the Principal Coordinate Analysis (PCoA) ordering method. The present study recorded 387 and 320 species in forest fragments and continuous forest, respectively. Myrcia splendens (Sw.) DC. (916 individuals), Ocotea longifolia Kunth (649), Casearia javitensis Kunth (623), Siparuna guianensis Aubl. (464) and Lacmellea arborescens (Mull.Arg.) Markgrave (416) showed to be the species with the largest number of indivduals representing 18% of the two environments (FF an CF) total. The mean test showed there to be a difference in the locally unique species, wich ocurred in the continuous forest with greater intensity. As to the species richness, Alter do Chão forest fragments show to harbor many arboreal species that are to be found in the continuous forest. Structurally, mean breast height diameter (BHDM) and total basal area (BAT) exhibited negative relation with continuous forest distance (DCF). The similarity revealed two groups (GI and GII), where GII was exclusively made up by fragments’ plots. Fragments differ compositionally from the continuous forest, but show to be structurally similar to each other. The forest fragments’ alpha diversity (α) variation showed positive correlation with their area and, the regression was significant (r²=0.32; p= 0.012). Nonmetric multidimentional scaling (NMDS) ordination pointed out most forest fragments samples to stay separate from the continuous forest, evincing separation to be greater than what expected at random by the analysis of similarity (ANOSIM: r= 0.2883; p= 0.002). PCoA analysis findings using multiple regression analysis indicated that the fragments’ size, distance to the continuous forest and from the water had acted significantly in the community ordering (r²=0.29; p= 0.017), displaying nesting pattern with the adjusted model. The species substitution pattern multiple regression, also showed to be significant (r²=0.60; p= 0.000049), with the distance to the continuous forest having the greatest influence (t= -4.31; p= 0.00031). The local diversity pattern showed to be best accounted for by beta diversity (ẞ) and the distance to the continuous forest was substantial when accounting for composition change and species substitution. Compositional specificity scores indicated the forest fragments furthest from the continuous forest to harbor species that are normally found on secondary forest.